PROPOSED MARKETING STRATEGY TO INCREASE NUMBER OF RETAIL INVESTOR (CASE STUDY: INDONESIA SEHAT MUTUAL FUND) - Pratama, Oktario
The National Health Insurance Program (JKN) is one of the Government's strategic programs, where the program is included in one of the Government's efforts to achieve the SDGs target in 2030. But for almost 6 years implementation, this program experiencing fluctuations, especially in terms of health care financing, which in the period 2015 to 2019 the Social Security Fund experienced a deficit of trillions of rupiah. one of the contributors to the Social Security Fund deficit is due to the large amount of arrears in contributions, especially in the independent participant segment. Various efforts were made by BPJS Kesehatan to reduce arrears of independent participants' contributions, ranging from socializing to the public regarding the payment of JKN contributions, expansion of contribution payment channels (in collaboration with third parties), auto debit contributions (in collaboration with banks, fintech and e-commerce services), telecolecting, sms blast, email blast and through Kader JKN. These efforts were quite successful in reducing the number of participants who had arrears less than 12 months. However, this effort was not effective for participants with 12-24 months arrears, where the majority of participants were unable to pay off arrears due to ability to pay problems. The Indonesia Sehat Fixed Income Mutual Fund is a business innovation launched by BPJS Kesehatan through collaboration with three Investment Managers, namely PT Bahana TCW Investment Management, PT Danareksa Investment Management, and PT Mandiri Manajemen Investasi. One of the benefits of this product is the donation feature which is intended to help JKN participants who have difficulty paying off their outstanding contributions. In its development, donations given by Indonesia Sehat mutual funds to the Social Security Fund also fluctuated. These fluctuations are affected by the amount of funds managed in Indonesia Sehat mutual funds, or better known as Asset Under Management (AUM). In mid-2019, there was a significant decrease in the amount of AUM, which also has a significant impact on the decrease in Social Security Fund donations. When the Covid-19 pandemic hit, there was a phenomenon in the Capital Market where the number of Retail Investors increased significantly. Not only on stock instruments, the increase in the number of retail investors also occurs in mutual fund instruments. Even until the middle of 2021, investment funds in fixed income mutual fund instruments are the largest compared to other mutual fund instruments. But this condition is inversely proportional to Indonesia Sehat mutual funds, where in these products there is no increase in the amount of AUM as happens in the industry. Allegedly, one of the causes of the inhibition of the growth of Healthy Indonesian mutual funds is because this product does not focus on retail investors. This research focuses on how BPJS Kesehatan can implement effective strategies to increase the number of retail investors in Indonesia Sehat mutual fund products. In this study, an external and internal analysis was used, using tools and frameworks such as PEST, Porter Five Forces, Competitor Analysis, Marketing Mix (7P’s), VRIO (Valuable, Rare, Imitation and Organized), and supported by interviews and surveys to internal BPJS Kesehatan. From the results of external and internal analysis, then mapping the strengths, weaknesses, opportunities, and threats through the SWOT Matrix. In the process of formulating a new marketing strategy, the STP framework and TOWS Matrix are used. One of the most important findings from the results of this study is the low awareness of potential investors towards Indonesia Sehat mutual fund products, which is allegedly due to the low marketing activities that have been carried out so far. From the results of external and internal analysis, then the mapping of strengths, weaknesses, opportunities, and threats is carried out through the SWOT Matrix. Author recommends a solution to change the marketing strategy in order to increase the number of retail investors based on the strategy formulation using the TOWS Matrix. The results obtained four strategic recommendations that can increase awareness and knowledge of potential investors about Indonesia Sehat mutual fund products. It is hoped that by increasing awareness and knowledge of potential investors, it will encourage an increase in the number of retail investors and the AUM of Indonesia Sehat mutual funds.